Kafka and Organization Studies - Lohmeyer, Nora; Schuessler, Elke S. (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Organisation scholars frequently refer to Franz Kafka to shed light on various dark sides of organisations, in particular the dysfunctional aspects of bureaucratic organisations commonly associated with the word “Kafkaesque.” In this essay, we take the hundredth anniversary of Franz Kafka’s death as an occasion to revisit his work and life as a source of imagination for organisation scholars. We start by introducing Kafka’s “office writings,” produced during his daytime job as an accident insurance lawyer for industrial workers and, so far, largely overlooked by organisation scholars, as well as facets of his biography. We then propose that a more comprehensive analysis of Kafka’s oeuvre offers organisation scholarship a unique perspective on two pressing, contemporary challenges of organising. First, Kafka’s work and life illuminate the inherent contingency and futility of organising in the face of uncertainty, while also highlighting its necessity. Second, his writing provides a nuanced understanding of enigmatic, inescapable organisations that resonate with today’s digital and algorithmic forms of organising. Through his work, we find examples of individual and organisational acts of resilience and resistance, including a leveraging of bureaucratic institutions to fight inequality and injustice. These themes directly speak to current debates on the role of organisation in times of crisis and disruption, marked by the erosion of democratic institutions, the rise of digital and algorithmic organizing, and ecological collapse.
Keywords: Bureaucracy; Contingency; Crisis; Kafka; Organisation Study; Organisationality